WCB is a C2 domain protein defining the plasma membrane - sub-pellicular microtubule corset of kinetoplastid parasites. - Baines, A; Gull, K (2008)
WCB is a protein that locates between the inner face of the plasma membrane and the sub-pellicular corset of microtubules in Trypanosoma brucei. We provide the molecular identity of WCB and bioinformatic analysis suggests that it possesses a C2 domain implicated in membrane/protein interactions and a highly charged region possessing characteristics of a putative tubulin-binding domain. Functional analyses via RNA interference (RNAi) depletion show that WCB is essential for cell morphogenesis. Depletion results in gross abnormalities in cell shape, mainly at the cytoskeletal/plasma membrane dynamic posterior end of the trypanosome. Failures in cytokinesis and zoid production are also evident. Furthermore, electron microscopy reveals that RNAi-induced trypanosomes lose local plasma membrane to microtubule corset integrity.